The role of SII and SIRI as Predictors of in-Hospital Mace in Acute Myocardial Infarction - Anitya Maretta Barus; Dewi Indah Sari Siregar; Ranti Permatasari; Almaycano Ginting; Muhammad Riza Lubis; Yasmine Fitrina Siregar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Major adverse cardiac events (MACE) are a leading cause of morbidity and mortality in acute myocardial infarction (AMI). Systemic inflammation plays a key role in atherosclerosis, plaque rupture, and thrombosis. The Systemic Immune-Inflammation Index (SII) and Systemic Inflammation Response Index (SIRI) are novel biomarkers that may support early risk stratification, but data from Indonesia are limited. Objective to assess the association between SII, SIRI, and MACE in AMI patients at Adam Malik Hospital, Medan. Methods: This cross-sectional study used a total sampling technique, including 224 AMI patients hospitalized from January–December 2023. SII and SIRI were calculated from neutrophil, lymphocyte, monocyte, and platelet counts. MACE during hospitalization was recorded. Mann–Whitney U and logistic regression were used (p < 0.05). Of 224 patients, 79.5% were male with a mean age of 56.49 years. STEMI accounted for 63.8% of cases, and hypertriglyceridemia was the most common comorbidity (27.2%). MACE occurred in 57 patients (25.4%), including 15 deaths (6.7%). Mean SII was 1090.52 and mean SIRI was 3.83. Both SII (p = 0.002) and SIRI (p = 0.001) were significantly associated with MACE. SIRI predicted MACE with an OR of 1.233 (95% CI: 1.151–1.320). SII and SIRI are significantly associated with MACE in AMI, but only SIRI shows predictive value for adverse outcomes.